1987
DOI: 10.1111/j.1365-2125.1987.tb03160.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐monodesmethyldiltiazem is the predominant metabolite of diltiazem in the plasma of young and elderly hypertensives.

Abstract: 1 Twelve young (ages 30-39 years) and twelve elderly (ages 65-83 years) hypertensives were administered diltiazem twice daily for 2 weeks at doses up to 240 mg day-'.2 Plasma was analysed for diltiazem, N-monodesmethyldiltiazem, and desacetyldiltiazem concentrations after a single 10 min intravenous infusion of 21.8 mg diltiazem HCl on day 1 and after the morning oral dose of 120 mg diltiazem base on day 14. 3 N-monodesmethyldiltiazem accumulated to higher plasma concentrations than desacetyldiltiazem at stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…This conclusion is supported by the facts that the observed free plasma concentrations of MA are much lower than its K i (Mayhew et al, 2000), and plasma levels of MD appear to be negligible (Molden et al, 2003). In addition, a prolonged half-life of diltiazem was observed in hypertension patients taking multiple doses (Montamat and Abernethy, 1987), consistent with a time-dependent autoinactivation of diltiazem metabolism. In fact, CYP3A is the major isoform responsible for N-demethylation reactions of diltiazem (Sutton et al, 1997).…”
Section: Discussionsupporting
confidence: 70%
“…This conclusion is supported by the facts that the observed free plasma concentrations of MA are much lower than its K i (Mayhew et al, 2000), and plasma levels of MD appear to be negligible (Molden et al, 2003). In addition, a prolonged half-life of diltiazem was observed in hypertension patients taking multiple doses (Montamat and Abernethy, 1987), consistent with a time-dependent autoinactivation of diltiazem metabolism. In fact, CYP3A is the major isoform responsible for N-demethylation reactions of diltiazem (Sutton et al, 1997).…”
Section: Discussionsupporting
confidence: 70%
“…They suggested that an alteration of CsA metabolism by diltiazem was unlikely and that a decrease in apparent volume of distribution was a more probable explanation. Our findings with diltiazem also suggest that inhibition of CsA metabolism is unlikely given that peak diltiazem concentrations approximate to 1 FLM (Montamat & Abernethy, 1987).…”
Section: Resultssupporting
confidence: 54%
“…The apparent k inact value (0.012 min -1 ) obtained for diltiazem using 0.2 mg/ml protein in the inactivation incubation underpredicted inactivation in hepatocytes ( Table 1 ) [34] and may lead to a conclusion that diltiazem is a remote time-dependent inactivator. Diltiazem is known to cause pharmacokinetic DDI in vivo [71,72] . Therefore, if M I is more potent inactivator, caution should be taken when rank ordering the TDI potential of NCEs based on parameters generated for parent inactivator under certain incubation conditions.…”
Section: Microsomal Time-dependent Inactivation Parameters Of Parent mentioning
confidence: 99%